1982
DOI: 10.1002/j.1460-2075.1982.tb01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Defective expression of mouse adenovirus Fl in human cells.

Abstract: HeLa cells infected with mouse adenovirus strain Fl (AdFl) produce at least 2000 times less virus than permissive mouse 3T3 cells. Viral DNA synthesis, however, proceeds unimpaired. The defect in virion production was linked to a dramatic reduction in the synthesis of AdFI structural proteins, in particular the hexon. The identity of the AdFl hexon gene product was recognized through its immunogenic reactivity towards an antiserum raised against the human adenovirus type 2 (Ad2) hexon gene product. This cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…As pointed out above, this line of reasoning ignores the presence of different terminal proteins on these templates. We have previously shown that Ad2 and AdFl DNA show very little homology (Antoine et al, 1982). It is thus to be expected that the primary sequences of these two proteins, which, as demonstrated here, are distinguished by a size difference of -8 kd, are very different from each other.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…As pointed out above, this line of reasoning ignores the presence of different terminal proteins on these templates. We have previously shown that Ad2 and AdFl DNA show very little homology (Antoine et al, 1982). It is thus to be expected that the primary sequences of these two proteins, which, as demonstrated here, are distinguished by a size difference of -8 kd, are very different from each other.…”
Section: Discussionsupporting
confidence: 50%
“…We have previously shown that Ad2 and AdFl DNA show very little homology (Antoine et al, 1982). In the respective heterologous systems, they are totally inactive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations